Bathyraja multispinis, Multispine Skate - Pollom, R. (2020)
The Multispine Skate (Bathyraja multispinis) is a medium-sized (to 126 cm total length) skate that occurs in the Southeast Pacific Ocean from Coquimbo, Chile to Cape Horn and in the Southwest Atlantic Ocean from Santa Catarina, Brazil to Tierra del Fuego and the Falkland Islands (Malvinas) and is demersal on the continental and insular shelves and slopes at depths of 70-740 m. It is captured in demersal trawl and longline fisheries that operate throughout its range and there is little refuge at depth; it is likely to be retained for sale for human consumption in the Southwest Atlantic, but is discarded dead in the Southeast Pacific. Across its range, skates are typically not recorded or managed at the species level, and there are no estimates of population size. In Argentina, there are no species-specific data, but rays in general declined in catch-per-unit-effort (CPUE) in the 1990s and early 2000s. In the Falkland Islands (Malvinas) target skate fishery, this species showed an either stable or increasing trend in CPUE over the time-series from 1994 to 2013. Overall, due to the level of inadequately managed fisheries it is exposed to, general declines of skates in some parts of its range, and its lack of refuge at depth, balanced with the increase in CPUE in the Falkland Islands (Malvinas), it is suspected that this skate has undergone a population reduction of 20-29% over the past three generations (45 years). Therefore, the Multispine Skate is assessed as Near Threatened, nearly meeting the threshold for Vulnerable A2bd.